2019
DOI: 10.1016/j.cell.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes and Community Turnover Differentially Shape the Global Ocean Metatranscriptome

Abstract: SummaryOcean microbial communities strongly influence the biogeochemistry, food webs, and climate of our planet. Despite recent advances in understanding their taxonomic and genomic compositions, little is known about how their transcriptomes vary globally. Here, we present a dataset of 187 metatranscriptomes and 370 metagenomes from 126 globally distributed sampling stations and establish a resource of 47 million genes to study community-level transcriptomes across depth layers from pole-to-pole. We examine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
400
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 319 publications
(427 citation statements)
references
References 129 publications
(170 reference statements)
25
400
2
Order By: Relevance
“…3) is coherent with the importance of this variable, as TARA Oceans sampled a wider temperature range (range ≈ 0-30°C, mean ≈ 21°C, SD ≈ 7°C) than Malaspina (range ≈ 15-30°C, mean ≈ 24°C, SD ≈ 3°C). Furthermore, and consistent with our results, recent global-scale studies reported strong correlations between ocean-microbiota composition (predominantly prokaryotic) and temperature, and weak correlations with nutrients [56,57]. In sum, the previous agrees with our results indicating that temperature is one of the most important agents exerting abiotic selection on the surface-ocean microbiota, although we cannot rule out the selective action of other unmeasured abiotic factors.…”
Section: Discussionsupporting
confidence: 92%
“…3) is coherent with the importance of this variable, as TARA Oceans sampled a wider temperature range (range ≈ 0-30°C, mean ≈ 21°C, SD ≈ 7°C) than Malaspina (range ≈ 15-30°C, mean ≈ 24°C, SD ≈ 3°C). Furthermore, and consistent with our results, recent global-scale studies reported strong correlations between ocean-microbiota composition (predominantly prokaryotic) and temperature, and weak correlations with nutrients [56,57]. In sum, the previous agrees with our results indicating that temperature is one of the most important agents exerting abiotic selection on the surface-ocean microbiota, although we cannot rule out the selective action of other unmeasured abiotic factors.…”
Section: Discussionsupporting
confidence: 92%
“…The higher abundance of Cluster 1 and Cluster 2 transcripts in few (three) stations must be interpreted carefully because the abundance of metatranscriptomic reads does not solely and directly reflect the differential expression of a gene. Transcript abundance is also a function of the bacterial abundance and maybe biased by several technical issues such as difference of coverage between samples (Salazar et al ., ). As an example, the apparent overexpression of Cluster 1‐ hgcA in the Marquesas Islands could result from oversequencing at these stations.…”
Section: Resultsmentioning
confidence: 97%
“…We aim to resolve the paradox between several biogeochemical evidences for in situ MeHg production and the absence of known anaerobic Hg methylating prokaryotes in the open ocean. Metagenomic and metatranscriptomic data from 243 and 187 Tara Oceans samples, collected from 68 and 108 open ocean locations covering most ocean basins respectively, were analysed to generate an ocean microbial reference gene catalogue (Sunagawa et al ., ; Salazar et al ., ). We screened the Tara Oceans metagenomes and metatranscriptomes for the presence of the key hgcA methylating gene.…”
Section: Introductionmentioning
confidence: 97%
“…As described previously 31 20-200 m). The sampling strategy and methodology have been described elsewhere 35 .…”
Section: Sample and Environmental Data Collectionmentioning
confidence: 99%
“…Previous studies have provided an overview of the microbial taxonomic diversity in the Arctic 16,20,[24][25][26] , including functions relevant to the ecosystem, like nitrification processes 15,27 , heterotrophy 13,21,24 or photoheterotrophy 28,29 . Finally, the uniqueness of polar environments has been evidenced when studying global biogeographical patterns by means of amplicon sequencing 30 or metagenomics and metatranscriptomics 31 . Recent technological advances such as the reconstruction of genomes from metagenomes are allowing to go beyond the community level and explore the functional capabilities of specific taxa.…”
Section: Introductionmentioning
confidence: 99%